The effects of genetic polymorphisms and diabetes mellitus on the development of peripheral artery disease - Zafer Yalım; Serap Tutgun Onrat; Sümeyra Alan; Mustafa Aldemir; Alaettin Avşar; İsmet Doğan; Ersel Onrat (KARE Publishing, 2020)
Objective: Peripheral artery disease (PAD) is a condition caused by the narrowing of limb arteries due to atherosclerosis. In recent years, polymorphisms in a number of genes have been shown to contribute to the risk of PAD development. However, whether the contribution of these inheritable factors is independent of traditional cardiovascular risk factors remains unclear. This study was an investigation of the effects of diabetes mellitus (DM) and genetic background, examined singly and together, on the pathogenesis of PAD. Methods: The effects of the factor V Leiden (G1691A), factor V H1299R, prothrombin G20210A, factor XIII V34L, B-fibrinogen -455 G>A, PAI-1 4G/5G, HPA1, MTHFR C677T, MTHFR A1298C, ACE I/D, APO B R3500Q, and APOE polymorphisms were evaluated using a cardiovascular disease strip assay (CVD StripAssay). Two groups were created: 100 patients with PAD (50 with DM, 50 without DM) and 60 controls without PAD (30 with DM, 30 without DM). Results: There was a significantly greater presence of the MTHFR A1298C and PAI 4G/5G homozygous polymorphisms in the PAD patients compared with the control group (p=0.035, p=0.004, respectively). There were no significant associations between the other genotypes and polymorphism frequencies. In the presence of DM, the PAI-1 4G/5G homozygous polymorphism was linked to the formation of PAD (p=0.021). Regression analysis indicated that the PAI-1 4G/5G gene homozygous polymorphism demonstrated a 17.1 times greater risk for DM with PAD [95% confidence interval (CI): 2.113-138.660; p=0.008] and the MTHFR A1298C homozygous polymorphism demonstrated a 316.6 times greater risk (95% CI: 10.763-9315.342; p<0.001) for the possibility of DM with PAD. Conclusion: The MTHFR A1298C and PAI 4G/5G homozygous polymorphisms may be associated with the development of PAD. The presence of the PAI 4G/5G homozygous polymorphism with DM was a powerful predictor for the development of PAD.